SISTEM PELAKSANAAN DISKRESI SECARA HUKUM OLEH KEPOLISIAN SEBAGAI APARAT PENEGAK HUKUM DALAM PEMOLISIAN YANG DEMOKRATIS - Joy Christ Prilendo Sembiring (Ilmu Hukum Prima (IHP), 2022)
The application of discretion is the policy of the office that essentially allows public officials (including the police) to carry out policies that violate the law, on three conditions, namely in the public interest, still within the limits of their jurisdiction, and do not violate the General Principles of Good Government. Data analysis is done qualitatively by collecting primary, secondary and tertiary legal materials related to research. The results of the analysis obtained are: the concept of police discretion as a law enforcement officer in the future in democratic policing is characterized by reforms from within the police body itself, namely through structural aspects, instrumental aspects and cultural aspects. The existing laws and regulations in the regulation of the performance of the State Police of the Republic of Indonesia, especially in the discussion of discretion, are adequate and there is no overlap between one law and another. It takes understanding of the police in interpreting and applying the provisions of existing rules so as not to become a negative assessment in the community due to improper abuse of police authority in the implementation of discretionary resolving cases. That it required oversight both internally and externally of police performance both personally and in groups. It can also be by improving the quality of police resources by means of formal education or training so as to build a responsible attitude to maintain the image of the police in the community and in accordance with the assessment of the Code of Ethics of the State Police of the Republic of Indonesia.